Analysing Procedures and Teachers’ Perception of Project-Based Learning in the Kurikulum Merdeka Framework - Lathifah, Hana; Prastyo, Yanuar (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2024)
This study explores the implementation of Project-Based Learning (PjBL) in the English subject as part of Kurikulum Merdeka at SMAN 9 Bandar Lampung, with a focus on both the procedure and the teachers' perceptions. Utilizing a qualitative research method, data were collected through questionnaire and interviews. The aim of the study is to investigate how PjBL is applied in the classroom setting and to gain insight into teachers' views on its PjBL application in Kurikulum Merdeka. The findings provide an in-depth understanding of the implementation process, including strategies used by teachers, and highlight the perceived benefits and obstacles encountered during the application of PjBL in Kurikulum Merdeka. These insights may contribute to enhancing the quality of PjBL practices in English language teaching, especially in Kurikulum Merdeka.